INFLUENCE OF ACUTE URAEMIA ON PERCUTANEOUS ABSORPTION OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS - Priborsky, Jan; Takayama, Kozo; Nagai, Tsuneji (Biomedical papers, 1998)
The influence of uraemia on percutaneous absorption of three model drugs (diclofenac, ibuprofen and indomethacin) whichare eliminated entirely via nonrenal route was investigated in the rats. Following day after bilateral nephrectomy (BUNlevels were between 30-50 mmol/l), gel ointment containing drugs under test was applied on the abdominal site of theskin. Comparing with the sham operated controls the percutaneous absorption significantly decreased in all three challengedsubstances. Influence on percutaneous absorption of indomethacin was investigated more in depth as this compound canserve as a model for other nonsteroid anti-inflammatory drugs. The 50 mmol/l concentration of urea (equal to uraemia)added to the gel ointment did not influence percutaneous absorption while 10 % concentration of urea decreasedpercutaneous absorption of indomethacin approximately 5 times. Solubility of indomethacin increased in the presence of10% urea in the gel more than two times. Elimination ratios Q0 were estimated to find if there is any effect onpharmacokinetics linked directly to the renal elimination. None of such changes were observed.
Keywords: Uraemia / Percutaneous absorption / Physical chemical properties